Imidazolium-based ionic liquids as modulators of corrosion inhibition of SDS on mild steel in hydrochloric acid solutions: experimental and theoretical studies. Issue 16 (21st January 2015) - Yousefi, Ali; Javadian, Soheila; Dalir, Nima; Kakemam, Jamal; Akbari, Jafar
Abstract : Surface interaction and corrosion processes of imidazolium-based ionic liquids and their mixtures with SDS on a mild steel surface. Abstract : The inhibition performance of six cationic ionic liquids (ILs); 1-ethyl-3-methylimidazolium chloride (EMIm Cl), 1-butyl-3-methylimidazolium chloride (BMIm Cl), 1-butyl-3-methylimidazolium hexafluorophosphate (BMIm PF6 ), 1-butyl-3-methylimidazolium tetrafluoroborate (BMIm BF4 ), 1-butyl-3-methylimidazolium bromide (BMIm Br), and 1-hexyl-3-methylimidazolium chloride (HMIm Cl) and their mixtures with an anionic surfactant, sodium dodecyl sulfate (SDS), was investigated using electrochemical impedance spectroscopy (EIS), potentiodynamic polarization (PDP), atomic force microscopy (AFM), dynamic light scattering (DLS), Fourier transform infrared spectroscopy (FT-IR) and quantum chemical calculations. Using these ILs, which differ in counter ion or chain length, allowed investigation of counter ion types and tail length effects on inhibition efficiency. The results show that formation of a three-dimensional hydrogen bond network between imidazolium rings and their counter ions can effect the corrosion behavior on mild steel. Among the studied ILs, HMIm Cl exhibited the best inhibition efficiency. Moreover, the theoretical quantitative structure activity relationship (QSAR) methods were used to predict the inhibition efficiency. Solutions of ILs/SDS mixtures showed good inhibition properties compared to solutions of individual surfactant and ILs, due to strong adsorption on the metal surface and formation of a protective film. In ILs/SDS mixed systems, the attractive electrostatic interaction between them is an advantage for vesicle or wormlike micelle formation, leading to an increase in inhibition efficiency. It is clear from the DLS results that the average aggregate size appears to increase with increasing chain length. The interaction between ILs/SDS on the metal surface (in the solid–liquid interface) was analyzed on the basis of regular solution theory. The results demonstrated that attractive interactions between ILs and SDS were strong in the solid–liquid interface. The flow effect was studied using a rotating disc electrode (RDE). The results confirmed that aggregates formed of ILs/SDS interaction are not stable and separated from the surface under flow condition. Metal surface characterization was performed using AFM and FT-IR. Potentiodynamic polarization investigations indicated that the studied inhibitors were mixed type inhibitors. Adsorption of the inhibitors on the mild steel surface obeyed the Langmuir adsorption isotherm. Furthermore, adsorption (Δ G 0ads) free energy in mixtures decreased compared to single ones.